(untitled) (Journal of Economic Additions, 2026)
This study evaluates the desert tourism sector in Ghardaïa (2015-2024) using a dual descriptive-statistical approach to assess supply-demand dynamics. While findings confirm a wealth of unique heritage assets (e.g., UNESCO-listed M’zab Valley) and expanding infrastructure, a significant performance gap remains. The sector suffers from structural inefficiencies, including suboptimal occupancy rates and sluggish investment realization. To bridge this gap, the research recommends a paradigm shift toward a sustainable, integrated development framework. This strategy must focus on enhancing operational efficiency and leveraging Ghardaïa’s cultural authenticity to transform its potential into a competitive regional tourism product. Jel Classification Codes: L83, Z32, R11